Evaluasi Keberhasilan Implementasi Sistem Informasi Manajemen Berbasis Cloud di Perusahaan Multinasional - Ermiannur; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Cloud-based Management Information Systems (MIS) are becoming increasingly popular solutions for multinational companies, thanks to their ability to store, manage and access data in real-time. This research aims to evaluate the success of cloud-based SIM implementation, focusing on technical, managerial and organizational aspects, as well as the challenges faced during the implementation process. The research method used is a combination of quantitative and qualitative approaches, with data collection through surveys and in-depth interviews with 50 multinational companies and 10 managers from IT and operational divisions. It is hoped that the research results will provide insight into the factors that influence the successful implementation of cloud-based SIM and offer recommendations for increasing the effectiveness of these systems in multinational companies.